THE ROLE OF NAJIM DAVKARAEV IN FOLK SCIENCE: RESEARCH AND DISCUSSION (TAMADDUN NURI JURNALI, 2024)
The article examines the scientific views, concepts and scientific activities of N. Davkarayev, the founder of Karakalpak folkloristics. N. Davkarayev is a researcher who collected samples of folklore and diligently tried to convey them to the people through a theoretical and methodological approach.